2023
DOI: 10.7759/cureus.47558
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asthma With Patients Diagnosed With Metabolic Syndrome: A Cohort Study in a Tertiary Care Hospital

Jishna G,
Elen Abraham,
Ghanshyam Verma
et al.

Abstract: IntroductionAsthma is defined as a chronic inflammatory airway disease. The prevalence of both asthma and obesity has been rising simultaneously, demonstrating a parallel trend. Obesity is a significant factor in metabolic syndrome, and numerous studies have indicated a connection between metabolic syndrome and bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The findings of Klop et al (2013) [ 30 ], Lin et al (2022) [ 18 ], Salimzadeh et al (2016) [ 35 ], Reed et al (2017) [ 34 ], and Kim et al (2011) [ 41 ] showed a positive correlation with the findings of the present study. Jishna et al (2023) [ 42 ] in their study mentioned the importance of hyperlipidemia control for the treatment of asthma secondary to metabolic syndrome, a consequence of iIR.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of Klop et al (2013) [ 30 ], Lin et al (2022) [ 18 ], Salimzadeh et al (2016) [ 35 ], Reed et al (2017) [ 34 ], and Kim et al (2011) [ 41 ] showed a positive correlation with the findings of the present study. Jishna et al (2023) [ 42 ] in their study mentioned the importance of hyperlipidemia control for the treatment of asthma secondary to metabolic syndrome, a consequence of iIR.…”
Section: Discussionmentioning
confidence: 99%